Nationwide Socioeconomic Status After Introduction of Mechanical Thrombectomy: A Hopeful Outlook on Timely Treatment for Ischemic Stroke. (16th November 2020) - Patel, Pious D; Salwi, Sanjana; Shannon, Chevis; Fusco, Matthew; Chitale, Rohan V
Abstract: INTRODUCTION: A 2003–2011 National Inpatient Sample (NIS) study revealed that low socioeconomic status (SES) patients were less likely to receive timely-reperfusion during acute ischemic stroke (AIS) treatment. Mechanical thrombectomy (MT) allows a wider treatment window which may improve access to timely treatment. METHODS: Patients with primary ICD-9-diagnosis code for AIS were identified from 2012–2015 NIS. Primary outcomes were timely-treatment (admission day MT/tPA), timely-MT (admission day MT), and functional outcome ("bad" = death or long-term facility disposition). Primary variable was zip code median income quartile ("4" = highest income). Covariates included age, race, gender, distance to hospital (home rurality versus hospital rurality), comorbidities, stroke severity, hospital size/region, payer, and transfer status. Multiple logistic regression was utilized to model timely-treatment and timely-MT within overall population, and functional outcome within MT-treated subset. RESULTS: Total of 40, 935 AIS patients were included (median age 70, 47.4% female, 73.3% White). Total of 25, 402 (62.1%) patients received timely-treatment, while 4, 126 (10.1%) received timely-MT. Income quartile-4 (OR = 1.2[1.0-1.3], P = . 007) was associated with timely-treatment after adjustment. Income quartile-4 was associated with timely-MT (OR = 1.2[1.1-1.3], P = . 002), but lost significance after adjustment with distance to hospital. Within both populations, low SES groups had > 4-fold increased rate of rural-to-urban hospital travel ( P < . 001). Within MT cohort, income quartile-3 was associated with better functional outcome (OR = 1.2[1.0-1.5], P = . 047), but lost significance after adjustment. CONCLUSION: Low SES was associated with lower rate of any timely-treatment, but was not associated with timely-MT or functional outcomes after adjustment. With increasing MT utilization, improving transfer rules, and "Get With the Guidelines" efforts, it will be important to continue measuring nationwide changes in SES disparities within AIS treatment.